Students’ Attributions on Performance in Examinations: A Study of different Secondary School Categories in Nyeri County, Kenya - Githui , Perminus; Njoka , Johannes (African Journal of Education,Science and Technology (AJEST), 2022)
Students’ attributions regarding the causes of their success or failure in examinations has continued to exercise the minds of educationists and policy makers in the world and Kenya in particular. There is a compelling need to address the fundamental basis of students’ attributions on their performance in order to provide appropriate and effective intervention measures with a view to boost their achievement. This study examined the students’ attributions on their academic attainment among different secondary school categories in Nyeri County, Kenya. The objectives of the study were to; assess the degree to which students ascribed their attributions on their performance in examinations to internal or external locus of control and compare students’ attributions by different school categories in secondary schools in Nyeri County in Kenya. The study tested the following null hypothesis H0I: There is no statistically significant difference in students’ attributions on own performance in examinations to external or internal locus of control and; H02: There is no statistically significant difference in students’ attributions by different school categories in secondary schools in Nyeri county in Kenya. The study adopted the descriptive survey research design. The target population consisted of 82,367 students in 245 secondary schools in Nyeri County, Kenya (Nyeri County office Education, 2018). The students were enrolled in different school categories as follows; national (6,531), county (29,184), subcounty (38,081) and private (8,571) secondary schools. The study adopted the stratified random sampling technique. Krecjie and Morgan (1971) sampling formula was used to determine the sample size of 384 respondents which was proportionately distributed to the four school categories as shown in Table 1. Data collection employed the use of a questionnaire on the sampled students. Two schools that were not earmarked for the research were used for pilot study with a sample of 36 students to test the reliability of the instrument. The Cronbach’s coefficient alpha was computed on pilot study data whose results was r= 0.801 which was higher than the Kerlinger 0.7 recommended threshold of acceptance. Both the descriptive and inferential statistics were used to analyze data with the aid of the SPSS version 20.0. Results of data analysis established that learners in national, sub-county and private secondary schools attributed their performance in examinations to internal locus of control while students in county schools attributed to external locus of control. Results of hypothesis testing (Ho1) established that the differences were not statistically significant (P= 0.200, α< 0.05) in the attributions of students to internal or external locus of control from the four school categories in Nyeri County. The study further revealed that students in national, sub-county and private secondary schools attributed performance in examination to internal locus of control while students in county schools attributed their performance to external locus of control. The results of hypothesis testing (Ho2) established that the observed differences by school categories were statistically different (P= 0.200, α< 0.05). This implied that the differences in students’ attributions on their performance in examinations by school categories was not statistically significant. The study concludes that the internal or external locus of control have a bearing on students’ attributions on their performance in examinations. The study recommends the need to strengthen the students’ psychosocial support systems such as coaching, mentorship, guidance, counseling and psychoeducation in providing assistance to students in order to shape their attributions especially towards acquisition of internal locus of control t hat involves taking responsibility of their actions.